Pengaruh Stres Kerja Dan Konflik Kerja Terhadap Kinerja Karyawan Pt. Infiltraco Murni Serang Banten - Taqwin, Ratona Ahsani, Dr. Rini Kuswati, S.E., M.Si (2017)
Performance assessment system can be defined as a system that is systematic and routine process for evaluating the performance of human resources and provide feedback on the performance of human resource planning come. One view is crucial maintained in human resource management is that every job can reach the level of mental maturity, intellectual, and psychological. This study aimed to examine the effect of work stress on employee performance, labor conflicts Determine the influence on employee performance, to know the effect of work stress and conflict work simultaneously on the performance of employees of PT Infiltraco Pure Serang Banten. Based on the test results of the above hypothesis, suggesting that job stress has a significant negative influence on employee performance. The results of this study showed that the higher the stress of working the lower the performance of the employee, by the above hypothesis test results, showing that the labor conflict had a significant negative influence on employee performance. The results of this study show that with increasing labor conflict happens, the lower the performance of the employee. Based on the test results hipotesisdi above, shows that stress kerjadan labor conflict jointly have a significant influence on employee performance. The results of this study show that with increasing work stress and work conflict happens, the lower the performance of the employee.